Clinical Course of Chronic Pancreatitis During Pregnancy and its Effect on Maternal and Fetal Outcomes. (27th March 2021) - Mahapatra, Soumya Jagannath; Midha, Shallu; Teja, Gadella Varun; Vajpai, Tanmay; Singh, Nilanchali; Sahoo, Sushree Monika; Pandey, Shivam; Elhence, Anshuman; Sethia, Rahul; Garg, Pramod Kumar
Abstract : Introduction: There are limited data on the effect of chronic pancreatitis (CP) on pregnancy outcomes and vice versa. Our aim was to evaluate the clinical trajectory of CP during pregnancy and its effect on pregnancy outcomes. Methods: All female patients of child-bearing age (≥15 years) diagnosed with CP were studied from January 2004 to July 2019. The change in frequency of painful episodes was assessed before, during, and after pregnancy. Maternal and fetal outcomes were compared between pregnant women (early onset) and women presenting with CP after completion of all pregnancies (late onset). Results: Of 187 women with CP, pregnancy outcomes and clinical course were assessed in 99 patients. The frequency of painful exacerbations was significantly lower during pregnancy compared with prepregnancy and postpregnancy periods ( P < 0.001). The median pain score decreased significantly to 0 (0–2) during pregnancy from 3 (0–6) before conception and increased to 4 (0–8) after pregnancy ( P = 0.002). Women with early onset CP (n = 57) had their first child later and had fewer pregnancies compared with those with late onset CP (n = 42). There was no difference in maternal outcomes such as gestational diabetes, hypertension, and preterm delivery, and fetal outcomes such as abortion, low birth weight, and still birth between the groups. There was no reported congenital anomaly. DISCUSSION: Younger patients with CP had later and fewer pregnancies, but there was no increased risk of adverse maternal and fetal outcomes. The clinical course of CP was usually benign during pregnancy with decreased frequency and severity of pain.